New host records of fungi - TEOTIA, R.S. (Indian Phytopathology, 2002)
Botryodiploidea theobromae is reported on leaves of Lawsonia alba [L. inermis] and Meliola amphitricha is reported on leaves of Mussanda frondosa in West Bengal, India.